2022
DOI: 10.1021/jacs.2c07061
|View full text |Cite
|
Sign up to set email alerts
|

High Nitrile Yields of Aerobic Ammoxidation of Alcohols Achieved by Generating O2 and Br Radicals over Iron-Modified TiO2 Photocatalysts

Abstract: Catalytic ammoxidation of alcohols into nitriles is an essential reaction in organic synthesis. While highly desirable, conducting the synthesis at room temperature is challenging, using NH 3 as the nitrogen source, O 2 as the oxidant, and a catalyst without noble metals. Herein, we report robust photocatalysts consisting of Fe(III)-modified titanium dioxide (Fe/TiO 2 ) for ammoxidation reactions at room temperature utilizing oxygen at atmospheric pressure, NH 3 as the nitrogen source, and NH 4 Br as an additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 56 publications
0
21
0
Order By: Relevance
“…58,59 Among the current available technologies, titania has been widely utilized to harvest solar light at ambient temperature for photocatalytic elimination of VOCs due to its high oxidation capacity, non-toxicity, low cost, and chemical stability. [59][60][61][62] It is generally believed that anatase is more active than rutile, and yet the majority of current research efforts are devoted to studying the RF effect rather than the anatase size effect on the photocatalytic performance of ARM-phase titania, [15][16][17][18]63,64 which may be due to the fact that in most cases the anatase sizes, rutile sizes, and RFs of ARM-phase titania can be hardly changed independently without interference with each other. In the present work, as shown in Fig.…”
Section: Study Of the Relationship Between The Photocatalytic Perform...mentioning
confidence: 99%
“…58,59 Among the current available technologies, titania has been widely utilized to harvest solar light at ambient temperature for photocatalytic elimination of VOCs due to its high oxidation capacity, non-toxicity, low cost, and chemical stability. [59][60][61][62] It is generally believed that anatase is more active than rutile, and yet the majority of current research efforts are devoted to studying the RF effect rather than the anatase size effect on the photocatalytic performance of ARM-phase titania, [15][16][17][18]63,64 which may be due to the fact that in most cases the anatase sizes, rutile sizes, and RFs of ARM-phase titania can be hardly changed independently without interference with each other. In the present work, as shown in Fig.…”
Section: Study Of the Relationship Between The Photocatalytic Perform...mentioning
confidence: 99%
“…12 In a recent contribution, Zhu and Zhang prepared an iron-modified TiO 2 catalyst that selectively converts both benzylic and aliphatic alcohols to the corresponding nitriles in the presence of oxygen, ammonia, and 365 nm light (Scheme 3). 13 The results obtained with iron-doped TiO 2 catalyst could be improved by using NH 4 Br as an additive. The method provided good to high yields (up to ∼98%) of relatively simple substrates bearing alkyl, ether, and ester functionalities.…”
Section: Fe Catalysismentioning
confidence: 99%
“…22 Recently, Zhang et al reported the photocatalytic conversion of aromatic alcohols to arylnitriles with satisfactory yields over Fe-TiO 2 via aldehyde-imide intermediates under ultraviolet irradiation. 23 Encouraged by these limited examples, accessing arylnitriles with improved selectivity and universality under visible-light irradiation from biomassderived alcohols would be feasible, and it is greatly necessary to develop novel heterogeneous photocatalysts of high efficiency for generating desired reactive oxygen species to implement the sequential conversion process. Single-atom catalysts (SACs) are a class of promising heterogeneous materials for the high-efficiency utilization of metal species or active sites.…”
Section: Introductionmentioning
confidence: 99%